Mitochondrial HMG–CoA Synthase Deficiency - Arnedo, María; Ramos, Mónica; Puisac, Beatriz; Gil-Rodríguez, Ma Concepción; Teresa, Esperanza; Pié, Ángeles; Bueno, Gloria; Ramos, Feliciano J.; Gómez-Puertas, Paulino; Pie, Juan (IntechOpen, 2011)
None